Strategy of Space Utilization for Industrial Activities in Talang Kelapa Urban Area - Zarlin, Een; Nuzir, Fritz Akhmad (Universitas Bandar Lampung (UBL), 2025)
The lack of analysis in policy formulation for controlling spatial utilization due to industrial development may lead to unsustainable land use. Therefore, this study aims to formulate a spatial utilization control strategy for industrial development in the urban area of Talang Kelapa District, Banyuasin Regency. This research employs a mixed-method approach, integrating both qualitative and quantitative techniques. The analysis was conducted using the Analytic Hierarchy Process (AHP) method, supported by Expert Choice 11 software. The findings indicate that the priority strategies for controlling spatial utilization amid industrial expansion in Talang Kelapa District are as follows: development supervision and guidance (33%), regulations and standards related to spatial utilization control (21.6%), the establishment of sanction directives (18.5%), the delineation of control/industrial allocation zones (13.9%), and the provision of incentives and disincentives (13%). This study concludes that the recommended strategy for development supervision and guidance includes establishing an integrated supervision team for spatial planning, engaging the community in monitoring spatial utilization, conducting awareness programs, training, and workshops for industrial stakeholders and local communities on sustainable spatial planning, evaluating spatial utilization through realization assessments, and strengthening the capacity of Civil Servant Investigators (PPNS) in the field of spatial planning.